TPLATE Recruitment Reveals Endocytic Dynamics at Sites of Symbiotic Interface Assembly in Arbuscular Mycorrhizal Interactions - Russo, Giulia; Carotenuto, Gennaro; Fiorilli, Valentina; Volpe, Veronica; Faccio, Antonella; Bonfante, Paola; Chabaud, Mireille; Chiapello, Marco; Van Damme, Daniel; Genre, Andrea (Frontiers in Plant Science, 2019)
Arbuscular mycorrhizal symbiosis between soil fungi and the majority of plants is based on a mutualistic exchange of organic and inorganic nutrients. This takes place inside root cortical cells that harbor an arbuscule: a highly branched intracellular fungal hypha enveloped by an extension of the host cell membrane - the perifungal membrane - which outlines a specialized symbiotic interface compartment. The perifungal membrane develops around each intracellular hypha as the symbiotic fungus proceeds across the root tissues; its biogenesis is the result of an extensive exocytic process and shows a few similarities with cell plate insertion which occurs at the end of somatic cytokinesis. We here analyzed the subcellular localization of a GFP fusion with TPLATE, a subunit of the endocytic TPLATE complex (TPC), a central actor in plant clathrin-mediated endocytosis with a role in cell plate anchoring with the parental plasma membrane. Our observations demonstrate that Daucus carota and Medicago truncatula root organ cultures expressing a 35S::AtTPLATE-GFP construct accumulates strong fluorescent green signal at sites of symbiotic interface, along recently formed perifungal membranes and at sites of cell-to-cell hyphal passage between adjacent cortical cells, where the perifungal membrane fuses with the plasmalemma. Our results strongly suggest that TPC-mediated endocytic processes are active during perifungal membrane interface biogenesis - alongside exocytic transport. This novel conclusion, which might be correlated to the accumulation of of late endosomes in the vicinity of the developing interface, hints at the involvement of TPC-dependent membrane remodeling during the intracellular accommodation of arbuscular mycorrhizal fungi.